The relationship between young college students’ recognition of national COVID-19 crisis governance capabilities and the improvement of national identity: the mediating role of online participation in public health critical events - Xie, Jun; Zhu, Na; Tan, Jia; Gao, Hong (Frontiers in Public Health, 2024)
Improving the young college students' national identity is crucial for social stability and development during public health critical events such as COVID-19. Young college students' recognition of national COVID-19 crisis governance capabilities can influence their national identity, and online participation in public health critical events may serve as a crucial role this intricate relationship. To examine this possibility, this study established an intermediary model to test the role of online participation in public health critical events in young college students' recognition of national COVID-19 crisis governance capabilities and improvement of national identity. This cross-sectional survey study surveyed 3041 young college students in China using convenience sampling method. The results suggested that young college students' recognition of national COVID-19 crisis governance capabilities (r =0.729, P <0.001) and online participation in public health critical events (r =0.609, P <0.001) were positively correlated with improvement of their national identity. Online participation in public health critical events partially mediates the relationship between these two factors (Indirect effect estimate =0.196, P <0.001). The findings support government's efforts to improve young college students' national identity by enhancing their recognition of national COVID-19 crisis governance and encouraging their online participate in public health critical events.